(3dHGH GdBOGHs - (3GSGeI Hf efbP , GSGeI Hf eQTO Hf Ydj Hf ebdO Hf fUQ Hf efbP GdcfGfj GdcdHj, CHh GdeXaQ,J (B584 (3g` s ((3QLH GdMQjQj s)
(3ChdgG (B:s
(3HGH GdhUGjG hgj COH hCeQ HeYQha hUjI GdCehGJ ddCMjGA YfO GdehJ HMb jLH Ydjge COGDg s
(3BNQgG (B:s
(3eG ddYde ZGjI jOQcgG GdQGZH, hdG fgGjI jba YfOgG GdWGdH s
(3fSNI KGfjIs
(3JJab aj ChdgG eY GdfSNI GdChdis
(3HGNJdGa aj HYV GdCdaGX HChdgG agQS HCHhGH GdcJGHs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs